Frequency, associated features, and burden of neurological disorders in older adult inpatients in Brazil: a retrospective cross-sectional study - Aroldo Bacellar; Bruno B. Pedreira; Gersonita Costa; Telma Assis (BMC, 2017)
Abstract Background The burden of neurological disorders (NDs) in older adult inpatients is often underestimated. We studied diagnostic frequency and comorbidity of NDs among inpatients aged ≥60 years. We compared rates of hospital mortality, length of stay (LOS), and readmission with younger patient counterparts (aged 18-59 years) and older adult non-neurological patients. Methods This was a retrospective cross-sectional study of inpatients in a tertiary care center in Brazil. We compiled data for all patients admitted between 1 January 2009 and 31 December 2010, and selected those aged ≥18 years for inclusion in the study. We collected data for inpatients under care of a clinical neurologist who were discharged with primary diagnoses of NDs or underlying acute clinical disorders, and data for complications in clinical or surgical inpatients. Patients who remained hospitalized for more than 9 days were categorized as having long LOS. Results Older adult inpatients with NDs (n = 798) represented 56% of all neurological inpatients aged ≥18 years (n = 1430), and 14% of all geriatric inpatients (n = 5587). The mean age of older adult inpatients was 75 ± 9.1 years. Women represented 55% of participants. The most common NDs were cerebrovascular diseases (51%), although multimorbidity was observed. Hospital mortality rate was 18% (95% confidence interval [CI], 15-21) and readmission rate was 31% (95% CI, 28-35), with 40% of patients readmitted 1.8 ± 1.5 times. The long LOS rate was 51% and the median LOS was 9 days (interquartile interval, 1-20 days). In younger inpatients mortality rate was 1.4%, readmission rate was 34%, and long LOS rate was 14%. In older adult non-neurological inpatients, mortality rate was 22%, readmission rate was 49%, and long LOS rate was 30%. Conclusions Older adult neurological inpatients had the highest long LOS rate of all patient groups, and a higher mortality rate than neurological patients aged 18-59 years. Readmissions were high in all groups studied, particularly among older adult non-neurological inpatients. Improved structures and concerted efforts are required in hospitals in Brazil to reduce burden of NDs in older adult patients.